TRAYECTORIAS DE VIDA ASOCIADAS A LA HABITABILIDAD EN CALLE Y EL CONSUMO DE SUSTANCIAS PSICOACTIVAS DESDE LA SALUD MENTAL - Suárez Herazo, Lilibeth; Ardila Garcia, Angie Katheryne; Amaya Silva, Jenny Melissa (Universidad de Costa Rica, 2023)
In this article, the life trajectories of a group of young people with a history of living on the street and their relationship with the consumption of  psychoactive Substances (PAS) were analyzed through a qualitative study with a phenomenological approach. By means of a reasoning from medical, psychological and discursive points of view, the socio-economic conditions that generated the street background of the participants, which in turn allowed the construction of inclusion routes from the mental health and the social sphere.